RITUAL KAHARINGAN DAN KEGIATAN LADANG BERPINDAH MASYARAKAT DAYAK DARAT Dl KOTAWARINGIN BARAT - nfn Hartatik (Naditira Widya, 2009)
The Dayak Darat inhabits the southwestern part.of Kalimantan in Kabupaten Kotawaringin Barat. This community is called Dayak Darat because they lived in lowland, which is different to that of their neighboring Dayak who lives in the highland or river basin. The people of Dayak Darat are Kaharingan adherents who still preserve their tradition and continuously perform numbers of rituals until today such as babolin (healing), basasalak (warding of misfortune and in regard to harvesting, mortuary and shifting agriculture. The existence of the Sultanate of Kotawaringin in the proximity of the village of the Dayak Darat made a significant cultural-political impact toward the Dayak Darat. This article discusses the Kaharingan tradition, shifting cultivation, and the Sultanate's influences toward the Dayak Darat.